An empirical model of the environmental effect of FDI in host countries: Analysis based on Chinese panel data - Boqiong Yang; Jianguo Chen (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
From the 1970's, Foreign Direct Investment (FDI) flowed into host countries. With the development of economy in host countries the environment deteriorated. The overall goal of this paper is to estimate whether the impacts of FDI positive or negative on environment in host countries. To meet this overall goal, it is constructed a simultaneous system with data of 28 provinces in China (1992-2008). This system supposes the pollution indicators to be determined by economic scale, industrial composition and pollution density of a province, in which pollution density is created to estimate the environmental effect of FDI more exactly than traditional technological character. Also the domestic and foreign capital is tried to distinguish to make the pollution source clear. Based on a panel data of 28 provinces (1992-2008) with the three-stage least squares (3sls) estimator, the results of the system show that with the domestic investment, the environmental effect is positive, which means that FDI increases pollution emission. The direct environmental effect of FDI, which does not include domestic investment, is different decided by various pollution indicators.
Keywords: F23; F18; O13; 330; FDI; pollution emission; host countries